From the EU-South Korea to the EU-New Zealand free trade agreements: A path leading to a breakthrough in the enforcement of labour rights - Tyc, Aneta (Studia Iuridica Toruniensia, 2023)
The analysis of the path that led to a breakthrough in the European Commission’s thinking about trade policy in the context of enforcing labour rights turns out to be crucial for formulating further postulates regarding the content of new free trade agreements (FTAs). The arguments contained in the article focus on the problem of the lack of sanctions in FTAs of the fourth generation. The author discusses the EU-South Korea FTA, as it resulted in convening a Panel of Experts whose report contributed to the ratification of ILO Conventions nos. 29, 87 and 98 by South Korea. However, the amendment to Korean legislation has not fully implemented these Conventions. This resulted in a breakthrough in thinking about trade policy. The revision of views on the promotional approach presented by the European Commission was visible in the content of the new FTA concluded in 2022 with New Zealand. It rightly provides for the possibility of sanctions in the event of a serious violation of labour rights, which, according to the author, qualifies it as a FTA of the fifth generation. However, it does not mean that the FTA is perfect. Comparative legal research has led the author to formulate de lege ferenda postulates in this regard.